Application of ventilator-associated events (VAE) in ventilator-associated pneumonia (VAP) notified in Brazil (IMPACTO MR-PAV): a protocol for a cohort study - Alvaro Avezum; Adriano José Pereira; Viviane C Veiga; Haliton Alves De Oliveira Junior; Giovanna Marssola Nascimento; Daniela Laranja Gomes Rodrigues; Daniela Ghidetti Mangas Catarino; Filipe Teixeira Piastrelli; Maysa Yukari Cheno; Katia Cristina Camonda Braz; Lucas Bassolli Oliveira Alves; Alexandre Prehn Zavascki; et al. (BMJ Open)
Introduction Certain criteria for ventilator-associated events (VAE) definition might influence the type of an event, its detection rate and consequently the resource expenditure in intensive care unit. The Impact of Infections by Antimicrobial-Resistant Microorganisms - Ventilator-Associated Pneumonia (IMPACTO MR-PAV) aims to evaluate the incidence and diagnostic accuracy of ventilator-associated pneumonia (VAP) using the current criteria for VAP surveillance in Brazil versus the VAE criteria defined by the US National Healthcare Safety Network-Center for Diseases Control and Prevention (CDC) criteria.Methods and analysis The study will be conducted in around 15 centres across Brazil from October 2022 to December 2023. Trained healthcare professionals will collect data and compare the incidence of VAP using both the current criteria for VAP surveillance in Brazil and the VAE criteria defined by the CDC. The accuracy of the two criteria for identifying VAP will also be analysed. It will also characterise other events associated with mechanical ventilation (ventilator-associated condition, infection-related ventilator-associated complication) and adjudicate VAP reported to the Brazilian Health Regulatory Agency (ANVISA) using current epidemiological diagnostic criteria.Ethics and dissemination This study was approved by the Institutional Review Board under the number 52354721.0.1001.0070. The study’s primary outcome measure will be the incidence of VAP using the two different surveillance criteria, and the secondary outcome measures will be the accuracy of the two criteria for identifying VAP and the adjudication of VAP reported to ANVISA. The results will contribute to the improvement of VAP surveillance in Brazil and may have implications for other countries that use similar criteria.Trial registration number NCT05589727; Clinicaltrials.gov.